Implementation of the Compilation of Islamic Economic Law in Sharia Pawn in Indonesia - Setiawan, Iwan; Rusmani; Nurhaeti (International Journal of Science and Society, 2023)
Sharia Pawnshops in Indonesia manage sharia pawn businesses at both central and regional levels, guided by a Sharia Supervisory Board. Their services and human resources are optimized to achieve company goals. The products offered include Rahn Hasan, Rahn Flexi, Rahn Bisnis, Amanah vehicle installments, Arrum BPKB, Arrum Emas, Arrum Hajj, and Sharia Gold Installments. In a sharia pawn contract, items serve as collateral for loans, with maintenance and storage being the responsibility of the debtor (rahin). The costs for maintenance are determined by an ijarah contract, distinguishing sharia pawns from conventional ones. Development efforts include creating digital applications to compete with fintech. To attract millennials, Pegadaian Syariah enhances its promotional strategies on social media. Employees must have technical and general knowledge about sharia pawnshops and their products. Collaborating with fintech companies benefits both pawnshops and customers. The implementation of KHES in Sharia Pawnshops encompasses contracts, harmony, conditions, and operational mechanisms.